2014
DOI: 10.1177/1046496414532954
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Versus Non-Competitive Goals in Group Decision-Making

Abstract: This study presents results from a group decision task in which groups were assigned either a competitive or a non-competitive goal. A total of 20 groups were tasked with putting together a relay team either with the goal to maximize the chance to win or with the goal to maximize the sense of community. Interaction process analysis revealed that there were more positive reactions in groups with the non-competitive goal. Analysis of the content of the conversations showed all groups to go beyond information giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Meanwhile, there is no interaction between conscientiousness and non-competitive situation in influencing group decision quality. Previously, Löfstrand and Zakrisson (2014) found that the atmosphere of equality, warmth, and a sense of community that exists between groups in noncompetitive situations are associated with the group performance. When linked with the results of this present study, such an atmosphere makes no difference in the quality of decision outcomes between high-conscientiousness groups and low-conscientiousness groups.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there is no interaction between conscientiousness and non-competitive situation in influencing group decision quality. Previously, Löfstrand and Zakrisson (2014) found that the atmosphere of equality, warmth, and a sense of community that exists between groups in noncompetitive situations are associated with the group performance. When linked with the results of this present study, such an atmosphere makes no difference in the quality of decision outcomes between high-conscientiousness groups and low-conscientiousness groups.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the reliance on participants’ experiences and self-described cognition, as well as the statistical results, we consider interaction analysis an integrated mixed method. To date, seven previous studies published in Small Group Research have used interaction analysis (Beck & Keyton, 2009; Hare, 2010; Kauffeld & Lehmann-Willenbrock, 2012; Keyton & Beck, 2010; Klonek et al, 2020; Löfstrand & Zakrisson, 2014; Paskewitz & Beck, 2018).…”
Section: Mixed Methods Analysis Typesmentioning
confidence: 99%
“…For example, Peña and Hancock (2006) found that in video game groups, members used more relational messages than task, indicating a more relational purpose to the group. In other groups, the opposite ratio was found, suggesting differing fundamental purposes Löfstrand & Zakrisson, 2014). Third, certain types of messages have been associated with positive and negative group outcomes.…”
Section: Task and Relational Messages In Groupsmentioning
confidence: 97%